Nonlinearities between bank stability and income diversification: A dynamic network data envelopment analysis approach. (30th November 2022) - Ben Lahouel, Béchir; Taleb, Lotfi; Kossai, Mohamed
Graphical abstract: Highlights: A three stage dynamic network slacks-based measure model to assess bank stability. The PSTR model is accurate for testing nonlinear relationships. Overall negative nonlinear link between bank stability and income diversification. We highlight the "dark side" of overdiversification. Abstract: This study contributes to the ongoing debate about the cost-benefit tradeoff of income diversification in banking. Its main objective is to shed light on the non-linear effects of income diversification on the financial stability of a set of European commercial banks during the post-financial crisis period (2010–2019). From an efficiency perspective, we use a three-stage dynamic network slacks-based measure model to assess the financial stability of banks, including non-performing loans as a measure of risk that is carried over between two periods. Then, by performing a panel smooth transition regression model, we investigate the regime-switching behavior of the relationship between income diversification and bank stability by showing how these variables heterogeneously interact with each other. Our findings show that high levels of income diversification negatively and significantly impact bank financial stability regardless of the diversification index used. Important policy implications arise from our findings pertaining to the optimality of income diversification and financial stability of European banks.